Japanese Encephalitis DNA Vaccines with Epitope Modification Reduce the Induction of Cross-Reactive Antibodies against Dengue Virus and Antibody-Dependent Enhancement of Dengue Virus Infection - Kotaki T. (2023)
Infection with viruses belonging to the genus Flavivirus, such as Japanese encephalitis virus (JEV) and dengue virus (DENV), is a worldwide health problem. Vaccines against JEV and DENV are currently available. However, the dengue vaccine possibly increases the risk of severe dengue due to antibody-dependent enhancement (ADE). Moreover, the Japanese encephalitis (JE) vaccine reportedly induces cross-reactive ADE-prone antibodies against DENV, potentially leading to symptomatic dengue. Therefore, it is necessary to eliminate the risk of ADE through vaccination. In this study, we attempted to develop a JE vaccine that does not induce ADE of DENV infection using an epitope modification strategy. We found that an ADE-prone monoclonal antibody cross-reactive to DENV and JEV recognizes the 106th amino acid residue of the E protein of JEV (E-106). The JE DNA vaccine with a mutation at E-106 (E-106 vaccine) induced comparable neutralizing antibody titers against JEV to those induced by the wild-type JE DNA vaccine. Meanwhile, the E-106 vaccine induced 64-fold less cross-reactive ADE-prone antibodies against DENV. The mutation did not compromise the protective efficacy of the vaccine in the lethal JEV challenge experiment. Altogether, the modification of a single amino acid residue identified in this study helped in the development of an ADE-free JE vaccine.